Clinical utility and implementation of polygenic risk scores for predicting cardiovascular disease - Schunkert, Heribert; Di Angelantonio, Emanuele; Inouye, Michael; Patel, Riyaz S; Ripatti, Samuli; Widen, Elisabeth; Sanderson, Saskia C; Kaski, Juan Pablo; McEvoy, John W; Vardas, Panos; Wood, Angela; Aboyans, Victor; et al. (European heart journal, 2025)
Genome-wide association studies have revealed hundreds of genetic variants associated with cardiovascular diseases (CVD). Polygenic risk scores (PRS) can capture this information in a single metric and hold promise for use in CVD risk prediction. Importantly, PRS information can reflect the causally mediated risk to which the individual is exposed throughout life. Although European Society of Cardiology guidelines do not currently advocate their use in routine clinical practice, PRS are commercially available and increasingly sought by clinicians, health systems, and members of the public to inform personalized health care decision-making. This clinical consensus statement provides an overview of the scientific basis of PRS and evidence to date on their role in CVD risk prediction for the purposes of disease prevention. It provides the reader with a summary of the opportunities and challenges for implementation and identifies current gaps in supporting evidence. The document also lays out a potential roadmap by which the scientific and clinical community can navigate any future transition of PRS into routine clinical care. Finally, clinical scenarios are presented where information from PRS may hold most value and discuss organizational frameworks to enable responsible use of PRS testing while more evidence is being generated by clinical studies.Genome-wide association studies have revealed hundreds of genetic variants associated with cardiovascular diseases (CVD). Polygenic risk scores (PRS) can capture this information in a single metric and hold promise for use in CVD risk prediction. Importantly, PRS information can reflect the causally mediated risk to which the individual is exposed throughout life. Although European Society of Cardiology guidelines do not currently advocate their use in routine clinical practice, PRS are commercially available and increasingly sought by clinicians, health systems, and members of the public to inform personalized health care decision-making. This clinical consensus statement provides an overview of the scientific basis of PRS and evidence to date on their role in CVD risk prediction for the purposes of disease prevention. It provides the reader with a summary of the opportunities and challenges for implementation and identifies current gaps in supporting evidence. The document also lays out a potential roadmap by which the scientific and clinical community can navigate any future transition of PRS into routine clinical care. Finally, clinical scenarios are presented where information from PRS may hold most value and discuss organizational frameworks to enable responsible use of PRS testing while more evidence is being generated by clinical studies.